The accumulation characteristics and exploration potential of oil and gas in the back-arc basin of Japan under the background of high heat flow - Jian-qiang Wang; Jie Liang; Jian-wen Chen; Qing-fang Zhao; Yin-guo Zhang; Jian-wei Zhang; Sen Li; Chang-qing Yang; Jian Zhang; Jing Sun; Chuan-sheng Yang; Yong Yuan; et al. (China Geology, 2023)
The Sea of Japan is located in the southeast margin of Eurasia, in the triangle area of the western Pacific Ocean. Due to the interaction of the Pacific plate, Eurasian plate and Philippine plate, its tectonic environment is complex, forming a typical trench-arc-basin system. At present, 148 oil and gas fields have been discovered in Japan, with an oil and gas resource of 255.78×106 t, showing a good prospect for oil and gas exploration. Based on the previous research and the recently collected geological and geophysical data, the characteristics of tectonic-sedimentary evolution and geothermal field in the basins around the Sea of Japan are analyzed. The results show that the tectonic evolution of the basin is mainly controlled by plate subduction and back-arc oceanic crust expansion, and it mainly undergone four tectonic-sedimentary evolution stages: Subduction period, basin development period, subsidence period and compression deformation period. The overall heat flow value of Japan Sea is high, and it is distributed annularly along Yamato Ridge. The geothermal heat flow value is about 50–130 MW/m2, and the average heat flow is 75.9±19.8 MW/m2, which has a typical “hot basin”. The high heat flow background provides unique thermal evolution conditions for hydrocarbon generation, which leads to the high temperature and rapid evolution. The authors summarized as “early hydrocarbon generation, rapid maturity and shallow and narrow hydrocarbon generation window”. The type of oil and gas is mainly natural gas, and it mainly distributed in Neogene oil and gas reservoirs. The trap types are mainly structural traps, lithologic traps and composite traps. In addition, the pre-Neogene bedrock oil and gas reservoirs also show a good exploration prospect. The resource prospecting indicates that Niigata Basin, Ulleung Basin and kitakami Basin are the main target areas for future exploration and development.©2023 China Geology Editorial Office.